SP3 Protocol for Proteomic Plant Sample Preparation Prior LC-MS/MS - Mikulášek, Kamil; Konečná, Hana; Potěšil, David; Holánková, Renata; Havliš, Jan; Zdráhal, Zbyněk (Frontiers in Plant Science, 2021)
Quantitative protein extraction from biological samples, as well as contaminants removal before LC-MS/MS, is fundamental for the successful bottom-up proteomic analysis. Four sample preparation methods, including the ﬁlter-aided sample preparation (FASP), two single-pot solid-phase-enhanced sample preparations (SP3) on carboxylated or HILIC paramagnetic beads, and protein suspension trapping method (S-Trap) were evaluated for SDS removal and protein digestion from Arabidopsis thaliana (AT) lysate. Finally, the optimized carboxylated SP3 workflow was benchmarked closely against the routine FASP. Ultimately, LC-MS/MS analyses revealed that regarding the number of identifications, number of missed cleavages, proteome coverage, repeatability, reduction of handling time, and cost per assay, the SP3 on carboxylated magnetic particles proved to be the best alternative for SDS and other contaminants removal from plant sample lysate. A robust and efficient two-hour SP3 protocol for a wide range of protein input is presented, benefiting from no need to adjust amount of beads, binding and rinsing conditions, or digestion parameters.